2019
DOI: 10.5888/pcd16.180540
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Identification and Referral of Adults With Prediabetes to a Diabetes Prevention Program

Abstract: Purpose and ObjectivesCommunity programs to prevent or delay the onset of type 2 diabetes are effective, but implementing these programs to maximize their reach and impact remains a challenge. The American Medical Association (AMA) partnered with the YMCA of the USA, as part of a Centers for Medicare and Medicaid Innovation demonstration project, to develop, implement, and evaluate innovative quality improvement strategies to increase routine screening, testing, and referral of Medicare patients with prediabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 8 publications
3
34
0
Order By: Relevance
“…A large study led by the American Medical Association found 56% enrollment upon point-of-care referrals to the NDPP and 11% enrollment using a retrospective, algorithm-based approach to referrals. 16 These results are fully consistent with the first known study of NDPP uptake with provider referrals. 17 Despite the comparably low rate of engagement upon algorithmic referrals, the potential to automate this approach is important for scalability, as well as reducing provider burden to meet US Preventive Services Task Force recommendations to refer at-risk individuals to intensive lifestyle interventions.…”
Section: Increasing Provider Referrals To the Ndppsupporting
confidence: 88%
See 1 more Smart Citation
“…A large study led by the American Medical Association found 56% enrollment upon point-of-care referrals to the NDPP and 11% enrollment using a retrospective, algorithm-based approach to referrals. 16 These results are fully consistent with the first known study of NDPP uptake with provider referrals. 17 Despite the comparably low rate of engagement upon algorithmic referrals, the potential to automate this approach is important for scalability, as well as reducing provider burden to meet US Preventive Services Task Force recommendations to refer at-risk individuals to intensive lifestyle interventions.…”
Section: Increasing Provider Referrals To the Ndppsupporting
confidence: 88%
“…18,19 Relatively few point-of-care referrals to the NDPP are made currently. 16 First, many providers are unaware of the NDPP as a resource for their patients. A 2016 survey of over 1,200 primary care providers found that only 38% were aware of the NDPP, and fewer (23%) had referred patients to the program.…”
Section: Increasing Provider Referrals To the Ndppmentioning
confidence: 99%
“…Collaboration among pharmacists and others is critical to improve chronic disease outcomes, and pharmacists should be included in value-driven, collaborative models such as patient-centered medical homes and accountable care organizations. Furthermore, fostering strong relationships between physicians and pharmacists on care teams is well documented as critical to patient care (31). Specific to diabetes prevention, Medicare beneficiary enrollment in a PREVENTING CHRONIC DISEASE VOLUME 17,E90 PUBLIC HEALTH RESEARCH, PRACTICE, AND POLICY…”
Section: August 2020mentioning
confidence: 99%
“…Health care providers and systems, especially those in primary care, generated multiple examples of systems of care innovations, such as coordinating care for those with HIV infection (1), expanding screening for colorectal cancer through a Medicaid accountable care organization primary care learning collaborative (2), and linking primary care patients with farmers markets (3). A partnership between the American Medical Association and the YMCA, a Center for Medicare and Medicaid Innovation demonstration project, tested increased screening, testing, and referral of Medicare patients with prediabetes seen in primary care practices in 17 US communities to diabetes prevention programs at local YMCAs, supported by a toolkit of workflows and process maps (4). The team was able to achieve a 19% enrollment rate, noting higher referral rates for practices that used a prediabetes registry — an emerging better practice.…”
mentioning
confidence: 99%
“…The evaluation methods reported are striking for the predominance of mixed methods; the use of diverse data sources, including commercial health claims data sets (15,16), electronic health records (4), geotags (16), and new measures such as Facebook click-through rates (13); the use of well-established frameworks such as RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) (4); and for their high level of sophistication (10). Although it is possible to use simple evaluation methods when assessing the value of single components of a larger program (such as the comparative value of different social media methods [13]), evaluation of large, complex programs requires considerable expertise, planning time, and funding.…”
mentioning
confidence: 99%